2018
DOI: 10.3390/antibiotics7040107
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of a Chromatographic Method for the Quantification of Isoniazid in Urine of Tuberculosis Patients According to the European Medicines Agency Guideline

Abstract: Isoniazid is a drug that is widely used against tuberculosis. However, it shows high interpatient variability in metabolism kinetics and clinical effect, which complicates the prescription of the medication and jeopardizes the success of the therapy. Therefore, in a specific patient, the pharmacokinetics of the drug must be elucidated to decide the proper dosage and intake frequency to make the drug suitable for therapeutic drug monitoring. This can be performed by the quantification of the drug in urine as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Other studies qualitative 8 Reported ratios low. Poor diffusion in saliva noted [ 74 , 77 ] No data Rifapentine 6 Studies in patients with TB needed [ 28 ] 7 Urine C max , AUC not reported [ 47 ] No data No data Isoniazid 7 DBS and plasma concentrations were measured in the included study, but C max , AUC, and DBS-plasma ratio not reported [ 35 ] 7 Ratios not provided in quantitative studies [ 36 , 38 , 49 , 50 , 59 , 67 , 69 ]. Other studies qualitative 8 Wide range of reported ratios [ 50 , 74 , 77 ] 7 Wide range of reported hair concentrations at different timepoints [ 84 ] in one study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies qualitative 8 Reported ratios low. Poor diffusion in saliva noted [ 74 , 77 ] No data Rifapentine 6 Studies in patients with TB needed [ 28 ] 7 Urine C max , AUC not reported [ 47 ] No data No data Isoniazid 7 DBS and plasma concentrations were measured in the included study, but C max , AUC, and DBS-plasma ratio not reported [ 35 ] 7 Ratios not provided in quantitative studies [ 36 , 38 , 49 , 50 , 59 , 67 , 69 ]. Other studies qualitative 8 Wide range of reported ratios [ 50 , 74 , 77 ] 7 Wide range of reported hair concentrations at different timepoints [ 84 ] in one study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the paucity of studies regarding the added value of isoniazid TDM, most of the investigators have proved a large intra‐ and interindividual variability in isoniazid pharmacokinetics in tuberculosis patients . It was shown that some factors such as age, sex, gastrointestinal disorders and drug interactions affect the pharmacokinetics of isoniazid leading to response variation .…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants herbal medicines have shown decreased oxidative stress significantly leading to the prediction of positive role of antioxidant drugs during anti-TB treatment. [3] , [4] , [5] Isoniazid [6] (INH) is a very efficient remedy against M. tuberculosis recommended by WHO.…”
Section: Tuberculosis (Tb) Is Considered As a Global Emergency By World Health Organization (Who)mentioning
confidence: 99%
“…[36,37] Crystal data: C7H6O4•C6H7N3O (M = 291.26 g/mol), triclinic, space group P1 ̅ (no. 2), a = 3.7075 (6), b = 10.9505 (18), c = 15.966(3) Å, α = 101.366 (6), β = 95.706 (6), γ = 91.327(6)°, V = 631.72(18) Å 3 , Z = 2, T = 120 K, μ(Mo-Kα) = 0.12 mm -1 , Dcalc = 1.531 g/cm 3 , 8870 reflections with 2 ≤ 50° measured, 2229 unique (Rint = 0.050), 243 refined parameters, R1 = 0.038 on 1655 reflections with I > 2σ(I), wR2 = 0.093 on all data.…”
Section: X-ray Crystallographymentioning
confidence: 99%